Test of models for photon strength functions of electric dipole photoexcitation - V. A. Plujko; S. Goriely; O. M. Gorbachenko; K. M. Solodovnyk (Ядерна фізика та енергетика)
Closed-form models for photon strength functions for the description of photoabsorption cross section in the energy range 5 - 30 MeV for even-even nuclei are tested. The experimental database was prepared with systematic uncertainty less than 10 % from the EXFOR data. The uncertainties are estimated using the calculations of the photo cross sections within TALYS 1.6 code. The theoretical models are compared with experimental photoabsorption cross section data. The minimum of the least-square deviation and the root-mean-square deviation factor are used as a criteria comparison of the theoretical calculations with experimental data. It is shown that the simple modified Lorentzian model is the best approach for simulation of the photoabsorption cross section at the gamma-ray energies below ~ 30 MeV.